2009
DOI: 10.1007/s10439-009-9834-7
|View full text |Cite
|
Sign up to set email alerts
|

The Glenohumeral Capsule Should be Evaluated as a Sheet of Fibrous Tissue: A Validated Finite Element Model

Abstract: The function of the glenohumeral capsule has typically been evaluated by isolating several discrete, ligamentous regions during experimental and computational investigations. However, recent data suggests that the regions of the glenohumeral capsule have significant interactions and function multiaxially. Therefore, examining the function of the inferior glenohumeral ligament as a discrete structure may not be appropriate. The objective of this work was to validate the predicted strain distribution and deforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…The joint was moved to 608 of abduction; the path of internal-external rotation was then determined by applying a 3 N-m rotation moment and a 22 N compressive force. 16,27 The compressive force ensured that the humeral head was centered within the glenoid and simulated contributions to joint stability from the negative intra-articular pressure of the capsule and the rotator cuff muscles. The positions that most closely corresponded to 608 of abduction and 08, 308, and 608 of external rotation served as reference positions for the application of the anterior load.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The joint was moved to 608 of abduction; the path of internal-external rotation was then determined by applying a 3 N-m rotation moment and a 22 N compressive force. 16,27 The compressive force ensured that the humeral head was centered within the glenoid and simulated contributions to joint stability from the negative intra-articular pressure of the capsule and the rotator cuff muscles. The positions that most closely corresponded to 608 of abduction and 08, 308, and 608 of external rotation served as reference positions for the application of the anterior load.…”
Section: Methodsmentioning
confidence: 99%
“…Previous evaluations of the strain distributions in the anteroinferior capsule showed a wide variability among shoulders. 16,22,24,27 Therefore, strain ratios were computed by normalizing the maximum principal non-recoverable strain and strain during the simulated physical exams in each element to the peak non-recoverable strain and peak strain in the intact state, respectively, for each specimen. Any elements containing strain values less than the experimental repeatability of 3.5% 16 were set to zero, which allowed differences to be detected between the intact and injured states when elements that were initially unloaded became loaded following dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As CT attenuations only provide a scalar value at each point, many studies assume isotropic elasticity (164)(165)(166)(167)(168)(169), although anisotropic material properties have also been implemented using information within the voxel (170). The elastic moduli for early isotropic models have been homogeneous (171)(172)(173), but more recent studies have used inhomogeneous materials (8,164,165,170,174-178) as they have been found to be more accurate than the models using homogeneous material properties (9,179,180).…”
Section: The Finite Element Methodsmentioning
confidence: 99%
“…The 3D positions of the strain markers were recorded in the reference strain configuration, which was determined via inflation, using a three-camera motion tracking system (Spicatek, accuracy: 0.05 mm) [33]. Simulated clinical exams were then performed on each shoulder at 60deg abduction, and 0 deg, 30 deg, and 60 deg of external rotation by applying a 25 N anterior load to the humérus while maintaining a 22 N compressive load to center the humeral head on the gienoid [13,[33][34][35]. The 3D positions of the strain markers were recorded at these three joint positions with the loading conditions applied.…”
Section: In Vitro Deformation Of the Glenohumeral Capsulementioning
confidence: 99%